Keefektifan Perlakuan Air Panas dan Teh Guano terhadap Nematoda Aphelenchoides besseyi pada Benih dan Pengaruhnya terhadap Bibit Padi - Syarifah, Syarifah; Supramana, Supramana; Triwidodo, Hermanu (Jurnal Fitopatologi Indonesia, 2023)
The Effectiveness of Hot Water and Guano Tea Treatments on Aphelenchoides besseyi Nematode on Rice Seeds and Their Effects on the Growth of Rice SeedlingAphelenchoides besseyi is one of the important nematodes infecting rice and can significantly reduce yield and grain quality. The research aimed to obtain an effective method to control A. besseyi in rice seeds through hot water treatment and soaking in guano tea. The study was conducted on three varieties, i.e Pak Tiwi 1, Ciherang, and IPB 3S. Two treatments was evaluated, i.e. soaking the seeds on hot water (55 °C) and guano and soaking time at 5, 10, 15, 20, 25, and 30 minutes. Hot water treatment at 55 °C and guano tea effectively reduced the population of nematodes, but show different effect depending on the variety. In var. Pak Tiwi 1, hot water treatment is effectively reduced nematode population with 5-30 minutes soaking time, and the best of growth of rice seedling shown in 10 minutes soaking in hot water and 20 minutes soaking in control treatment. In var. Ciherang, the method of hot water treatment with 5-30 minutes soaking time and immersion of guano tea for 30 minutes effectively decreases the nematode population, and the best interaction that produces the highest rice seedling growth is shown in the control treatment with a time of 10, 15, 20, 25, and 30 minutes, immersion of guano tea with 5, 10, 25 minutes, and hot water treatment with 5 and 10 minutes soaking time. In IPB 3S, the best population decrease was shown in the immersion of guano tea with 5 and 30 minutes soaking time, meanwhile the best growth of rice seedling is shown in 5 minutes soaking time of hot water treatment.